The Politics of India under Modi An Introduction to India's Democracy, Economy, and Foreign Policy - Yadav, Vikash (Lever Press, 2023)
Since the right-wing, Hindu-nationalist government of Narendra Modi's Bharatiya Janata Party (BJP) came to power at the national level in 2014, and with its consolidation of power in the 2019 general election, India has witnessed a significant realignment of its national politics and a shift toward the right of the political spectrum. The Politics of India under Modi provides a detailed overview of India's political trends, economic prospects, and international relations in the twenty-first century. This book is designed as a supplement and update for existing syllabi that trace India's political economy from the birth of the republic to the quest for economic liberalization and great power status. Undergraduates and scholars interested in India's foreign policy and political reform will find value in this timely book. The subject of this book is extremely compelling and important, as well as timely. BJP rule and the Modi regime, it is now clear, represent some critical turning points in Indian politics, which have yet to be analyzed in depth academically by experts. I see this book as a key first step in this process. -Rina Verma Williams, School of Public and International Affairs at the University of Cincinnati